Not just blue sky [Herbert Kroemer]. - Perry, T.S.
From high-speed transistor to sold-state lasers, IEEE Medal of Honor recipient Herbert Kroemer's theories have led to a wealth of semiconductor applications. His theory of heterostructures did not immediately have practical use, but it is at the root of today's CD and DVD players, cellphones and even laser pointers. For his work on heterostructures, he was awarded the Nobel Prize for Physics in 2000. The article outlines Kroemer's career and gives a brief description of semiconductor heterostructures.
Keywords: Herbert Kroemer; IEEE Medal of Honor; Heterostructures; High-speed transistor; Semiconductor heterojunction; Sold-state lasers